INTEGRASI KEARIFAN LOKAL MELALUI CERITA RAKYAT DALAM MATA PELAJARAN BAHASA INDONESIA UNTUK MENUMBUHKAN KARAKTER MANDIRI SISWA MI ISLAMIYAH SUMURGENUK - Ditta Salafiyah; Khotimatus Sholikhah; Moh. Vito Miftahul Munif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the integration of local wisdom through folklore in Indonesian language learning and to identify the character values developed among students at MI Islamiyah Sumurgenuk. This study employed a descriptive qualitative approach. Data were obtained from the principal, Indonesian language teacher, and students through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing and verification. Data validity was ensured through source and technique triangulation. The results showed that the integration of local wisdom was implemented by connecting folklore with Indonesian language learning materials through activities such as reading or listening to stories, identifying characters, plots, settings, themes, and moral messages, conducting discussions, retelling stories, and identifying moral values. Folklore was not only used as learning material for language skills but also as a medium to introduce students to local culture and values of life. The character values developed included religiosity, cooperation, responsibility, hard work, social awareness, environmental awareness, discipline, gratitude, respect for others, self-confidence, and independence. Students' independence was reflected in their ability to complete assignments, seek information, express opinions, and attempt to solve difficulties before asking for assistance. Therefore, the integration of local wisdom through folklore can serve as a contextual alternative for Indonesian language learning that develops language skills while fostering students' character and appreciation of local culture.